Nonlinearity in Energy Harvesting Systems Micro- and Nanoscale Applications - Blokhina, Elena; El Aroudi, Abdelali; Alarcon, Eduard; Galayko, Dimitri (Springer International Publishing : Imprint: Springer, 2016)
This book is a single-source guide to nonlinearity and nonlinear techniques in energy harvesting, with a focus on vibration energy harvesters for micro and nanoscale applications. The authors demonstrate that whereas nonlinearity was avoided as an undesirable phenomenon in early energy harvesters, now it can be used as an essential part of these systems. Readers will benefit from an overview of nonlinear techniques and applications, as well as deeper insight into methods of analysis and modeling of energy harvesters, employing different nonlinearities. The role of nonlinearity due to different aspects of an energy harvester is discussed, including nonlinearity due to mechanical-to-electrical conversion, nonlinearity due to conditioning electronic circuits, nonlinearity due to novel materials (e.g., graphene), etc. Coverage includes tutorial introductions to MEMS and NEMS technology, as well as a wide range of applications, such as nonlinear oscillators and transducers for energy harvesters, and electronic conditioning circuits for effective energy processing. Provides a guide to nonlinearity in energy harvesting systems, implemented in micro- and nanoscale employing MEMS and NEMS engineering techniques; Begins with tutorial chapters that make the discussion self-contained and accessible to readers who are not familiar with MEMS and nonlinear dynamics; Includes an overview of electrostatic and piezoelectric transducers and discusses in detail conditioning circuits for vibrations energy harvesters.